Alternative approaches to labor values and prices of production: Theory and evidence - Deepankar Basu; Athanasios Moraitis (University of Massachusetts, Department of Economics, 2023)
In this paper, we discuss three approaches to estimating classical prices of production(long run equilibrium prices) in both a circulating capital model and a model that includes capital stock: the Standard Interpretation of Marx's value theory, the New Interpretation of Marx's value theory, and the Sraffian approach to prices of production. We add two refinements to both models: (a) allowing for differential wages rates across industries; and(b) taking account of unproductive industries in labor value calculations. We implement(a) the circulating capital models using harmonized input-output data from the World Input Output Database for 37 countries for the period 2000-2014, and (b) the model with capital stock for the U.S. economy using input-output and other relevant data for 2020.For all models, we estimate labor values, prices of production and the uniform rate of profit. We test for deviation between relative labor values and relative prices of production using both regression and non-regression-based methods. For both the circulating capital model and the model with capital stock, we find that the vector of relative labor values and the vector of relative prices of production are far apart in terms of both regression and non-regression-based measures.
Keywords: 330; labor value; price of production; uniform rate of profit; classical theory of prices